Clinical Research in Eight Constitution Medicine: A Scoping Review of Current Evidence - Younkuk Choi; Juhee Cho (Mary Ann Liebert, 2024)
Introduction: Understanding human differences is essential for managing chronic diseases. To establish robust evidence for Eight Constitution Medicine (ECM), a Korean personalized medical system, it is necessary to identify the status of clinical research in ECM and develop validated measurements. This study aims to confirm the types of clinical research on ECM and how they have been conducted. Methods: A scoping review covered three international databases (PubMed, Embase, and Cochrane) and five domestic electronic databases (DataBase Periodical Information Academic, Research Information Sharing Service, Korean Studies Information Service System, National Digital Science Library, and Oriental Medicine Advanced Searching for Integrated System), using strategies such as reference searches and gray literature searches. Mapping was attempted, and subcategories were established, synthesized, and presented in tables. All relevant content in Korean and English was considered, excluding theses, dissertations, and editorials. Results: Sixty ECM studies were selected. There were 47 (78.3%) original studies, of which 39 (65.0%) were observational and eight (13.3%) were experimental. There were six eight constitution diet (ECD)-related studies (12.8%), much less than the 15 (31.9%) eight constitution acupuncture (ECA)-related studies. Original studies that measured the effectiveness of ECM used various methods of exposure/intervention and outcome measurement tools. Conclusions: The original research evidence for ECM mainly came from observational studies on ECA and eight constitution diagnosis. Active clinical research related to ECD and a tool that effectively measures adherence and target diseases are required. Furthermore, it is necessary to introduce electronic patient-reported outcome measurements that can be used in community-based clinical environments.